2022
DOI: 10.1111/jnp.12302
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis reveals distinct patterns of saccade impairment and their relation to cognitive profiles in Parkinson's disease

Abstract: Saccade performance has been reported to be altered in Parkinson's disease (PD), however, with a large variability between studies as both motor and cognitive impairment interfere with oculomotor control. The aim of this study was to identify different patterns in saccade alterations in PD using a data-driven approach and to explore their relationship with cognitive phenotypes. Sixty-one participants with PD and 25 controls performed eye-tracking (horizontal and vertical prosaccades, antisaccades) and neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
2
0
0
Order By: Relevance
“…in the past to correlate with several measures of executive function, particularly on tasks that involve psychomotor speed, visual search, attention taskswitching, and inhibition, such as the TMTA and TMTB tests 38,39 , supporting the notion that the anti-saccade task taps into several executive and frontal cognitive processes, including but not limited to cognition inhibition [40][41][42] . These ndings as a whole are also consistent with the ndings of a recent study that used a cluster analysis to identify different patterns in saccade abnormalities in PD and their relationship with cognitive phenotypes 43 . The authors identi ed three clusters, one of which was de ned by a general disinhibition of re exive saccades (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…in the past to correlate with several measures of executive function, particularly on tasks that involve psychomotor speed, visual search, attention taskswitching, and inhibition, such as the TMTA and TMTB tests 38,39 , supporting the notion that the anti-saccade task taps into several executive and frontal cognitive processes, including but not limited to cognition inhibition [40][41][42] . These ndings as a whole are also consistent with the ndings of a recent study that used a cluster analysis to identify different patterns in saccade abnormalities in PD and their relationship with cognitive phenotypes 43 . The authors identi ed three clusters, one of which was de ned by a general disinhibition of re exive saccades (i.e.…”
Section: Discussionsupporting
confidence: 90%
“…These saccadic findings as a whole are also consistent with the findings of a recent study that used a cluster analysis to identify different patterns in saccade abnormalities in PD and their relationship with cognitive phenotypes 48 . The authors identified three clusters, one of which was defined by a general disinhibition of reflexive saccades (i.e.…”
Section: Discussionsupporting
confidence: 89%